2018
DOI: 10.1002/anie.201809302
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Properties of Hydrogen Atoms Adsorbed on M0‐Nanoparticles Suspended in Aqueous Solutions: The Case of Ag0‐NPs and Au0‐NPs Reduced by BD4

Abstract: The nature of H-atoms adsorbed on M 0 -nanoparticles is of major importance in many catalyzedr eduction processes.Using isotope labeling,wedetermined that hydrogen evolution from transient {(M 0 -NP)-H n } nÀ proceeds mainly via the Heyrovsky mechanism when nislarge (i.e., the hydrogens behave as hydrides) but mainly via the Tafel mechanism when niss mall (i.e., the hydrogens behave as atoms). Additionally, the relative contributions of the two mechanisms differ considerably for M = Au and Ag.T he results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 51 publications
(120 reference statements)
2
31
0
Order By: Relevance
“…The reduction of 4‐NP occurs by transferring electrons/hydrides/hydrogens from the donor BH 4 − to the acceptor NPs, and to the substrate 4‐NP after their adsorption/migration on the surface of the NPs. Recently, we demonstrated that with catalytic HER in the presence of M−NPs at high [BH 4 − ] levels as the reducing agent, H 2 is formed through the hydride pathway (Heyrovsky mechanism, Reaction 1) and that the Heyrovsky mechanism takes place to a greater extent on Ag NPs in comparison with Au NPs . This mechanism can be correlated to this work since the [BH 4 − ] used is high, and Ag NPs exhibit higher catalytic activity than Au NPs (Figures and S6).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The reduction of 4‐NP occurs by transferring electrons/hydrides/hydrogens from the donor BH 4 − to the acceptor NPs, and to the substrate 4‐NP after their adsorption/migration on the surface of the NPs. Recently, we demonstrated that with catalytic HER in the presence of M−NPs at high [BH 4 − ] levels as the reducing agent, H 2 is formed through the hydride pathway (Heyrovsky mechanism, Reaction 1) and that the Heyrovsky mechanism takes place to a greater extent on Ag NPs in comparison with Au NPs . This mechanism can be correlated to this work since the [BH 4 − ] used is high, and Ag NPs exhibit higher catalytic activity than Au NPs (Figures and S6).…”
Section: Resultssupporting
confidence: 73%
“…Recently, we demonstrated that with catalytic HER in the presence of MÀ NPs at high [BH 4 À ] levels as the reducing agent, H 2 is formed through the hydride pathway (Heyrovsky mechanism, Reaction 1) and that the Heyrovsky mechanism takes place to a greater extent on Ag NPs in comparison with Au NPs. [61] This mechanism can be correlated to this work since the [BH 4 À ] used is high, and Ag NPs exhibit higher catalytic activity than Au NPs (Figures 4 and S6). The fact that AgÀ Pt (9 : 1) alloy NPs are excellent catalysts for 4-NP reduction suggests that the catalyst holds electrons on its surface to form hydrides.…”
Section: Catalytic Study Of 4-nitrophenol Reductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Valuable mechanistic proposals have been published for the NP‐catalyzed hydrogen evolution from borohydride salts under various conditions, emphasizing the crucial role of the NP and NP−H bonds formation and evolution ,. Some proposals suggested oxidative addition [82 ] of a B−H bond to transfer a hydrogen atom onto the MNP and leave the negative charge onto the boron atom followed by electron transfer that may be subsequently used in further steps.…”
Section: Resultsmentioning
confidence: 99%